Exploration and Purification of Secondary Metabolites from Lactobacillus acidophilus and Their Potential as a Bio-preservative - Chaudhary, Anis Ahmad; Fareed, Mohammad (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The natural tendency of many food items to spoil requires the use of natural preservatives to extend shelf life while maintaining their original qualities, such as texture and flavour. Consequently, there's a rising demand for preservatives derived from organic sources. This research focused on producing a bioactive compound with a low molecular weight using Lactobacillus acidophilus (MTCC 10307). The study investigated how different production mediums, temperatures, and pH levels influenced the synthesis process. With optimized conditions, the molecule was synthesized, extracted, purified, and characterized. UV analysis detected an absorption peak characteristic of a proteinaceous substance in the extracted material. The isolated compound was then tested for its antibacterial activity against foodborne pathogens. By utilizing the isolated component as a bio-preservative in various types of juices, its effect on shelf life was assessed. One advantage of a low molecular weight compound is its ability to quickly penetrate cell walls and combat bacteria responsible for food spoilage.